The Influence of Brand Storytelling and Experiential Marketing on Purchase Decisions Mediated by Purchase Intention - Nadifa Fania Khuluqiya; Wahju Wulandari; Mulyono (Journal of Management Research and Studies, 2026)
This study aims to analyze the influence of brand storytelling and experiential marketing on purchase decisions through purchase intention among Generation Z consumers of Batik Tulis Celaket. The increasing preference of Generation Z for authentic brand experiences and meaningful interactions encourages businesses to adopt marketing strategies that strengthen consumer engagement and purchasing behavior. This research employed a quantitative explanatory approach. Data were collected from 125 consumers of Batik Tulis Celaket using a structured questionnaire. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that brand storytelling has a positive and significant effect on purchase decisions but does not significantly affect purchase intention. Experiential marketing has a positive and significant effect on both purchase intention and purchase decisions. In addition, purchase intention significantly influences purchase decisions. However, purchase intention does not mediate the relationship between brand storytelling and purchase decisions, nor the relationship between experiential marketing and purchase decisions. These findings suggest that experiential marketing plays a more prominent role in encouraging Generation Z consumers to make purchasing decisions, while brand storytelling contributes directly to purchase decisions without increasing purchase intention.